Wireless LED controller IC for smart contact lens system - Cheonhoo Jeon; Jahyun Koo (Electronics Letters, 2024)
Abstract This letter presents a wirelessly powered LED driving circuit for a smart contact lens system. Since photobiomodulation has been investigated for ocular disease treatment by irradiating light with a specific wavelength, a smart contact lens equipped with a µLED and its controller IC can be utilized as a phototherapy system. The proposed circuit design facilitates constant‐current generation to drive the LED and incorporates a wirelessly powered system. The system can be turned on and off in synchronization with an external wireless power source, providing controllability for the LED's irradiation period and intensity. The IC is fabricated in the 180‐nm CMOS process with a die area of 1.0 mm2 and integrated into the smart contact lens with an external loop antenna and a far red/NIR LED. The measurement demonstrates the irradiation period of the LED is successfully controlled by the external source, with current levels from 0.53 mA to 1.4 mA, thereby confirming the feasibility of the phototherapy system.